Cardiorespiratory diseases in an industrialized area: a retrospective population-based cohort study - Elisa Bustaffa; Cristina Mangia; Liliana Cori; Fabrizio Bianchi; Marco Cervino; Fabrizio Minichilli (BMC, 2023)
Abstract Background Atmospheric pollution has been recognized as the greatest environmental threat to human health. The population of the Venafro Valley, southern Italy, is exposed to emissions from a Waste-To-Energy (WTE) and a cement plant and potentially also to another WTE located in the neighboring region of Lazio; also, the vehicular atmospheric pollution situation is critical. In order to assess the environmental health risk of residents in eight municipalities of the Venafro Valley, a retrospective residential cohort study during 2006-2019 was carried out. Methods Four exposure classes were defined by natural-break method, using a dispersion map of nitrogen dioxides (chosen as proxy of industrial pollution). The association between the industrial pollution and cause-specific mortality/morbidity of the cohort was calculated using the Hazard Ratio (HR) through a multiple time-dependent and sex-specific Cox regression adjusting for age, proximity to main roads and socio-economic deprivation index. Results Results showed, for both sexes, mortality and morbidity excesses in the most exposed class for diseases of the circulatory system and some signals for respiratory diseases. Particularly, mortality excesses in both sexes in class 3 for diseases of the circulatory system [men: HR = 1.37 (1.04-1.79); women: HR = 1.27 (1.01-1.60)] and for cerebrovascular diseases [men: HR = 2.50 (1.44-4.35); women: HR = 1.41 (0.92-2.17)] were observed and confirmed by morbidity analyses. Mortality excesses for heart diseases for both sexes [men-class 3: HR = 1.32 (0.93-1.87); men-class 4: HR = 1.95 (0.99-3.85); women-class 3: HR = 1.49 (1.10-2.04)] and for acute respiratory diseases among women [HR = 2.31 (0.67-8.00)] were observed. Morbidity excesses in both sexes for ischemic heart diseases [men-class 3: HR = 1.24 (0.96-1.61); women-class 4: HR = 2.04 (1.04-4.02)] and in class 4 only among men for respiratory diseases [HR = 1.43 (0.88-2.31)] were also found. Conclusions The present study provides several not-negligible signals indicating mitigation actions and deserve further investigations. For future studies, the authors recommend enriching the exposure and lifestyle profile using tools such as questionnaires and human biomonitoring.